2021
DOI: 10.1021/acsami.1c07780
|View full text |Cite
|
Sign up to set email alerts
|

Split-Type Electrochemical Immunoassay System Triggering Ascorbic Acid-Mediated Signal Magnification Based on a Controlled-Release Strategy

Abstract: This research put forward a novel split-type electrochemical (EC) immunosensor which integrated the controlled-release strategy with EC detection for application in the field of biosensing. Concretely, ascorbic acid (AA) was packaged in a cadmium sulfide (CdS)-capped spherical mesoporous bioactive glass (SBG) nanocarrier (SBGCdS) on account of encapsulation technology. To reduce the complexity of the bioanalysis, the detection antibody-labeled SBGCdS–AA bioconjugate was applied in a 96-well microplate for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Herein, the EC impedance spectroscopy (EIS) test (Figure C) was applied to explore the designed Tri-Ag NPs TSC–GSH/GSSG NRMs and characterize the assembly process of the proposed EC sensing interface. , It could be observed that the semicircle domain of GCE/Nafion (curve a), GCE/Tri-Ag NPs TSC /Nafion (curve b), GCE/Tri-Ag NPs TSC–GSH /Nafion (curve c), and GCE/Tri-Ag NPs TSC–GSH/GSSG /Nafion (curve d) gradually expanded. Notably, there was an increase in the impedance of the Tri-Ag NPs TSC after being partially replaced by GSH.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the EC impedance spectroscopy (EIS) test (Figure C) was applied to explore the designed Tri-Ag NPs TSC–GSH/GSSG NRMs and characterize the assembly process of the proposed EC sensing interface. , It could be observed that the semicircle domain of GCE/Nafion (curve a), GCE/Tri-Ag NPs TSC /Nafion (curve b), GCE/Tri-Ag NPs TSC–GSH /Nafion (curve c), and GCE/Tri-Ag NPs TSC–GSH/GSSG /Nafion (curve d) gradually expanded. Notably, there was an increase in the impedance of the Tri-Ag NPs TSC after being partially replaced by GSH.…”
Section: Resultsmentioning
confidence: 99%
“…Linear anodic stripping voltammetry (LASV) 42,74,[128][129][130] and differential pulse anodic stripping voltammetry (DPASV) 66,[131][132][133] are the most prevalent techniques used in the literature for the final Ag oxidation step. However, some studies have used square wave anodic stripping voltammetry (SWASV) 36,40,55 and cyclic voltammetry (CV). 25,38,39 LASV is the most prevalent among these techniques because of its simplicity.…”
Section: Electrochemical Techniquesmentioning
confidence: 99%
“…21 Therefore, the NSE is one of the important biomarkers to be monitored. 22 Detection of NSE has been reported using various biosensing schemes, including surface plasmon resonance (SPR) spectroscopy, 23 surface plasmon-enhanced uorescence (SPF), 24,25 uorescence, 26 electrochemistry, [27][28][29] and photoelectrochemistry. 30,31 Nevertheless, most of the sensing methods rely on the development of nanomaterials that enhance or produce the sensor signals to detect NSE at its clinical threshold value.…”
Section: Introductionmentioning
confidence: 99%